Simple and Computer-assisted Olfactory Testing for Mice - Brai, Emanuele (J Vis Exp, 2015)
Olfaction is highly conserved among species and is required for reproduction and survival. In humans, olfaction is also one of the senses that is affected with aging and is a strong predictor of neurodegenerative diseases. Thus, olfaction testing is used as a non-invasive diagnostic method to detect neurological deficits early on. In order to understand the mechanisms underlying olfactory network susceptibility, olfactory research in rodents has gained momentum in the past decade. Here, we present a very simple, time efficient and reproducible olfactory testing method of innate odor perception and sensitivity in mice without the need of any prior food or water restriction. The tests are performed in a familiar environment to the mice, require only the scents and a 2 min session of odorant exposure. The analysis is performed, post-hoc, using computer-assisted commands on ImageJ and can be, therefore, carried out from start to end by one researcher. This protocol does not require any special hardware or setup and is indicated for any laboratory interested in testing olfactory perception and sensitivity.